Do sonho ao sim: a vulnerabilidade das mulheres no consumo dos ritos do casamento - Carvalho, Diana Lúcia Teixeira de (2012)
The objective of this study is to characterize the wedding consumption performed by women, during the liminal transition concerning the rite of passage, to identify emerging vulnerabilities that affect this consumption relation. In this way, theories were approached regarding the concepts of the consumer vulnerability, conspicuous consumption, consumption of rituals and liminal transition, to contextualize the relations between the wedding and possible experiences of vulnerable consumption, which resulted in a conceptual model of research. The adopted methodology was oriented by the interpretative paradigm with the use of qualitative approach. The chosen method was the videography, through individual interviews, primer technique, and observational videography, complementary and partially, which provide the combination of discourses about the consumption related to the wedding, seeking to understand the experiences of vulnerability, with the observations of the consumption situations experienced. Therefore, eleven women were interviewed, of which four were followed in certain interactions with providers. Subsequently, the transcriptions of the interviews and dialogs between the brides and the providers resulted in the following dimensions, based on the conceptual model of research: the wedding and the vulnerability of the brides in the consumption of the wedding rites. In every dimension are presented interrelated categories which were a result from the analyzed discourses based on discourse analysis. The results of this research indicate that experiences of vulnerability occur when the brides do not understand their preferences, which often make them unable to act on behalf of them. It is evidenced that the relations among the symbolic consumption, conspicuous consumption, consumption of rituals influence possible relations of vulnerable consumption and that the women emotional state is connect to the liminal transition during the wedding rite of passage. Nevertheless, the brides are not inert to situations of vulnerability, since it is possible to observe responses such as negotiation, adaptation and conformation.